Static and dynamic experimental study of strengthened inforced short concrete corbel by using carbon fabrics, crack path in shear zone - I. Ivanova; J. Assih (Fracture and Structural Integrity)
The paper presents an experimental analysis of tracking the path of the cracks and crack growth in strengthened or repair reinforced concrete short corbels bonded by carbon fiber fabrics under static and dynamic loads. The reinforced short concrete corbel is a used precast element, for industrial buildings and structures. In fact, their functioning interestingly unconventional is compared to classical beam type elements. Then the effects of bending and shearing are combined in this case. The horizontal reinforced steel is localized to resist to tensile strength induced in bending top and a transversal strength-absorbing contribution. The introduction of carbon fiber composite in the field of Civil Engineering allows to strengthen or repair reinforced concrete structures using adhesive. So the carbon fiber material has many advantages as its low weight, flexibility, easier handling and also interesting physicochemical properties. However maintenance of civil engineering works is to protect them by ensuring better sealing or limiting corrosion. Then strengthening is to repair structures by using bonding technique to compensate their rigidity loss and limit the cracking. This allows to improve their performance and durability. Bonding of composite material in tensile zone of corbel retrieves most tensile stress and allows the structure to extend their load-bearing capacity. The local behavior of the structure is measured by means of the extensometer technique based on electrical strain gauges. This technique allowed to measure strains of steel, carbon fiber fabrics and concrete. The results of this investigation showed that strengthened reinforced concrete corbel bonded by carbon fiber fabrics can improve the ultimate load to twice and stiffens less than a third. The ultimate load, strain and displacement of the specimen are compared to reference experimental model of monotonic and cyclic applied loads. The success of strengthening depends strongly on surface preparation conditions. The cracking mechanisms and collapse modes under static and dynamic loadings are presented. The strengthened reinforced concrete short corbel behavior can be presented in three areas: overall elastic area, crack propagation area and opening of diagonal crack area.